Research on the allocation mechanism of grassland ecological compensation among different industries based on ecosystem product value accounting - Li Ma; Yaojie Wu (PLoS ONE, 2026)
The manifestation and allocation of the positive externalities of grassland ecosystem products are critical to realizing the value of ecological compensation. Previous studies on ecological compensation have largely overlooked the heterogeneity of ecosystem products within regions and the differences in compensation among various industrial sectors, particularly the alignment and regulatory role between industrial structure and ecological compensation. In response, this study shifts the focus from interregional horizontal compensation to intraregional structural compensation, emphasizing the rational allocation mechanism of ecosystem product value among different industrial actors. Based on meteorological monitoring data and land-use data, the value of grassland ecosystem products is estimated using the water balance method and soil erosion equations. Furthermore, an inter-industry ecological compensation allocation model is constructed based on the consumption value of grassland ecosystem products and the proportion of industrial structure. The results show that: (1) From 2013 to 2023, none of the four major pastoral regions are required to bear ecological compensation for carbon sequestration and oxygen release consumed by the livestock industry; however, the average ecological compensation surplus decreased from 7.38 × 10⁸ CNY to 7.09 × 10⁸ CNY. (2) Most regions are required to bear ecological compensation for air purification consumed by the industrial sector, while some regions in Inner Mongolia and Xinjiang are also required to compensate for water conservation consumed by industry. (3) No region is required to bear ecological compensation for water conservation and soil retention consumed by the tourism industry; however, regions such as Turpan and Alxa are required to compensate for carbon sequestration and oxygen release consumed by tourism, with the average compensation increasing from 1.35 × 10⁶ CNY to 1.54 × 10⁷ CNY.